2011
DOI: 10.1016/j.polymdegradstab.2010.03.014
|View full text |Cite
|
Sign up to set email alerts
|

EVA-layered double hydroxide (nano)composites: Mechanism of fire retardancy

Abstract: Abstract:Composites of ethylene-vinyl acetate copolymer with two different layered double hydroxides have been obtained by melt blending and these have been characterized by X-ray diffraction, transmission electron microscopy, thermogravimetric analysis, thermogravimetric analysis connected to mass spectroscopy and cone calorimetry. There is some small difference in dispersion between the zinc-containing and the magnesiumcontaining layered double hydroxides in EVA, but both these are microcomposites with good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…MCC experiments were used to further analyze the correlation between the crosslinked structure and flammability for the cured benzoxazine resins . The key combustion parameters, including heat release capacity (HRC), total heat release (THR), peak heat release rate (PHRR) and the temperature for the PHRR ( T max ), were obtained.…”
Section: Resultssupporting
confidence: 57%
“…MCC experiments were used to further analyze the correlation between the crosslinked structure and flammability for the cured benzoxazine resins . The key combustion parameters, including heat release capacity (HRC), total heat release (THR), peak heat release rate (PHRR) and the temperature for the PHRR ( T max ), were obtained.…”
Section: Resultssupporting
confidence: 57%
“…Several recent studies have reported the somewhat unexpected detection of acetone as a pyrolysis product of EVA-MHs. This was initially described by Witkowski et al in 2012 and has since been corroborated by other research [8,9,10].…”
Section: Introductionsupporting
confidence: 61%
“…The use of LDH particles as nanofiller represents an emerging field of application, which may present advantages in comparison to montmorillonite, due to its versatility in chemical composition and charge density and allowing multiple interactions with the polymer [20]. Besides, the structure of these particles presents hydrox-ide groups in great number, making them attractive to enhance thermal stability and to improve fire resistant properties in polymer systems [21,22].…”
Section: Introductionmentioning
confidence: 99%